Vezérfonal a szintézisíráshoz II/1. A demokratikus kísérlet elbukása 1944–1948.: Első rész: A debreceni ideiglenes Nemzetgyűléstől a második köztársaság kikiáltásig, 1944. december 21–1946. február 1. - Gulyás, László (Közép-Európai Közlemények, 2025)
At the end of 1944, at the beginning of 1945, the Red Army conquered Hungary. By the summer of 1948, the Hungarian communist emerging from domestic illegality or returning from emigration is Moscow built up their dictatorship. All this happened on Stalin’s order, and with the help of the Soviet Union. In this study, we present a firs stage of this process. The starting point of the section we are examining is December 21 of 1944, when Provisional National Assembly began his deliberations. In while its end point is Februray 1 of 1946, when the second Hungarian Republic was proclaimed.